2014
DOI: 10.1021/ac501685v
|View full text |Cite
|
Sign up to set email alerts
|

Development of MSn in Digitally Operated Linear Ion Guides

Abstract: This publication demonstrates the use of digital waveform manipulation in linear ion guides to trap isolated ions and fragment them before mass analysis by time-of-flight mass spectrometry (TOF-MS). Ion trapping and collection was performed by waveform duty cycle manipulation to create a negative axial potential between the rods and the end-cap electrodes. Ion isolation can be performed by duty cycle manipulation to narrow the range of stable masses while continuing to axially trap the ions. Further ion isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…3 We also used the agility of DWT to create a new method of excitation that jumps the selected ions into the unstable region by changing the duty cycle or the frequency for a few cycles and then jumping back into the stable regions before the excited ions can escape, the isolated excited ions then undergo collision-activated dissociation in the same ion guide. 4 Our work demonstrated that the energy and motion of the ions can be precisely controlled merely by changing the duty cycle and frequency of the trap. It is the duty cycle that manipulates the stability diagrams of the ions in both the axial and radial directions.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…3 We also used the agility of DWT to create a new method of excitation that jumps the selected ions into the unstable region by changing the duty cycle or the frequency for a few cycles and then jumping back into the stable regions before the excited ions can escape, the isolated excited ions then undergo collision-activated dissociation in the same ion guide. 4 Our work demonstrated that the energy and motion of the ions can be precisely controlled merely by changing the duty cycle and frequency of the trap. It is the duty cycle that manipulates the stability diagrams of the ions in both the axial and radial directions.…”
Section: Introductionmentioning
confidence: 79%
“…This same methodology was used to preconcentrate specific low‐abundance ions to saturation for subsequent analysis in the same study . We also used the agility of DWT to create a new method of excitation that jumps the selected ions into the unstable region by changing the duty cycle or the frequency for a few cycles and then jumping back into the stable regions before the excited ions can escape, the isolated excited ions then undergo collision‐activated dissociation in the same ion guide …”
Section: Introductionmentioning
confidence: 99%
“…Duty cycle manipulation of DITs and guides can achieve the same utility without applying DC a potential between the waveforms. [3][4][5] A schematic diagram that defines all of the waveform parameters and the variables used in the calculation of the transfer matrix can be found in our previous publication. 5 The trace of the transfer matrix for a waveform with 50/0/50 duty cycle was plotted as a function of q for each orthogonal direction in a 3D digital ion trap in Figure 1.…”
Section: Calculating the Pseudopotential Well Depth For All Values Of Qmentioning
confidence: 99%
“…The method of ellipses, however, has not yet been applied to explore potential differences and similarities of sinusoidal and digitally operated quadrupole devices. Over the last decade, digital waveform technology has demonstrated its ability to meet and exceed the abilities of sinusoidal systems . The method of ellipses presents a method of comparison for these devices …”
Section: Introductionmentioning
confidence: 99%